2000
DOI: 10.1103/physreva.62.022712
|View full text |Cite
|
Sign up to set email alerts
|

Emission-line polarization degrees andnlmldistributions produced by state-selective electron capture in slowet al.

Abstract: Polarization degrees of lines emitted by Kr 7ϩ excited ions produced by single-electron capture during Kr 8ϩ ϩLi(2s) collisions were experimentally measured for projectile energies between 0.1 and 2.5 keV amu Ϫ1 . They were compared with theoretical polarization degrees obtained from nl m l distributions calculated by using the classical trajectory Monte Carlo ͑CTMC͒ method; radiative cascades have been included in the calculations. The fair agreement between experimental and calculated polarization degrees co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…where b is the impact parameter. Summation in (7) over magnetic substates m gives the nl-(subshell-)selective capture cross section, and summation over both m and l gives the n-(shell-)selective capture cross section. Obviously, the nlm-selective cross sections σ cx nlm are the most sensitive ones to the details of the electron capture dynamics.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where b is the impact parameter. Summation in (7) over magnetic substates m gives the nl-(subshell-)selective capture cross section, and summation over both m and l gives the n-(shell-)selective capture cross section. Obviously, the nlm-selective cross sections σ cx nlm are the most sensitive ones to the details of the electron capture dynamics.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Numerous experiments [4][5][6][7][8][9][10][11][12][13][14][15][16] have been devoted to the determination of photon polarization degrees in charge exchange collisions of ions with atoms and molecules. In the keV energy region, most of these experiments have measured the polarization degrees of light produced in singleelectron capture by highly charged ions from alkali atoms [4][5][6][7][8][9][10][11][12]. The polarization degrees were found to be large, 15 ∼ 40%.…”
Section: Introductionmentioning
confidence: 99%
“…This allows one to probe the collision dynamics on a more fundamental level. Numerous experiments have been devoted in the past [1][2][3][4][5][6][7][8] to the determination of photon polarization degree in collisions of multicharged ions with atomic and molecular targets. In the keV energy region, most of the experiments have measured the polarization of emitted radiation following the single-electron capture in collisions of highly charged ions with alkali-metal atoms [4][5][6], and polarization degrees of 15∼40% have been observed.…”
mentioning
confidence: 99%
“…Numerous experiments have been devoted in the past [1][2][3][4][5][6][7][8] to the determination of photon polarization degree in collisions of multicharged ions with atomic and molecular targets. In the keV energy region, most of the experiments have measured the polarization of emitted radiation following the single-electron capture in collisions of highly charged ions with alkali-metal atoms [4][5][6], and polarization degrees of 15∼40% have been observed. However, in the experimental studies involving the charge transfer processes of He-like C 4+ , N 5+ , and O 6+ ions with He and H 2 targets [5,7,8], it was found that the polarization degree for the 3p 2 P 3/2 -3s 2 S 1/2 transition lies in two regions: 0∼7% for the O 6+ + He and N 5+ + H 2 collisions, and 17-21% and 16-24% for the N 5+ + He and C 4+ + H 2 collision systems, respectively.…”
mentioning
confidence: 99%
“…The information about the magnetic substate population allows one to probe the collision dynamics on a more fundamental level. Numerous experimental [1][2][3][4][5][6][7][8] and theoretical [9,10] studies have been devoted to the determination of photon polarization degree in collisions of multicharged ions with atoms and molecules. However, in the environment of hot dense plasmas, the Coulomb interaction between charged particles is screened which obviously affects the dynamics of atomic collision processes.…”
Section: Introductionmentioning
confidence: 99%